1374. Integrated Safety Summary of Omadacycline: A Novel Aminomethylcycline Antibiotic. (26th November 2018) - Opal, Steven; File, Thomas M; Van Der Poll, Tom; McGovern, Paul; Tzanis, Evan; Chitra, Surya
Abstract: Background: Omadacycline (OMC) is a novel aminomethylcycline with activity against Gram-positive, many Gram-negative, anaerobic, and atypical pathogens. It is in clinical development as once-daily oral (PO) and intravenous (IV) monotherapy for acute bacterial skin and skin structure infections (ABSSSI) and community-acquired bacterial pneumonia (CABP). Cumulative safety results from Phase 3 clinical trials are reported. Methods: This pooled safety analysis is based on 2, 150 subjects: OASIS-1 ( N = 645), OASIS-2 ( N = 735) in ABSSSI; OPTIC ( N = 770) in CABP. Comparators were linezolid (LZD) 600 mg IV then PO in ABSSSI ( n = 689); moxifloxacin (MOX) 400 mg IV then PO in CABP ( n = 388). Safety parameters included treatment-emergent adverse events (TEAEs), laboratory evaluations, vital signs, and electrocardiogram (ECG) findings. Results: A total of 1, 073 subjects received OMC: 705 received OMC IV then PO (ABSSSI, n = 323; CABP, n = 382); 368 received OMC PO only for ABSSSI. Overall, 60.6% were male and 91.6% white; mean age ranges were 44.7–45.1 and 60.9–62.1 years in ABSSSI and CABP studies, respectively. TEAEs were observed in 47.5% (OMC), 41.2% (LZD), and 48.5% (MOX) of subjects, with gastrointestinal events the most common TEAEs. Serious TEAEs were low (3.6% OMC, 1.9% LZD, 6.7% MOX). Nausea (14.9% OMC, 8.7% LZD, 5.4% MOX) and vomiting (8.3% OMC, 3.9% LZD, 1.5% MOX) were the most frequently reported TEAEs. Diarrhea was observed in 2.4% OMC, 2.9% LZD, and 8.0% MOX subjects, with no cases of Clostridium difficile in OMC-treated subjects. Most TEAEs were mild to moderate and did not result in study drug discontinuation (3.1% OMC, 1.5% LZD, 7.0% MOX); 4 OMC, 1 LZD, and 0 MOX subjects discontinued for nausea and vomiting. Frequency of hepatic TEAEs was similar for OMC, LZD, and MOX: 4.3% OMC, 4.1% LZD, and 4.5% MOX subjects had post-baseline ALT >3× upper limit of normal. Vital signs and ECGs had comparable clinically notable values post-baseline in each treatment group. Known tetracycline class adverse events such as fungal infections were similar in all groups. Conclusion: Pooled analyses demonstrate a favorable OMC safety profile, consistent with its tetracycline heritage. OMC was generally well tolerated in subjects with ABSSSI and CABP, with infrequent treatment discontinuations. Disclosures: T. M. File Jr., BioMerieux: Consultant, Consulting fee; Curetis: Consultant, Consulting fee; Melinta Therapeutics: Consultant, Consulting fee; Merck: Consultant, Consulting fee; Motif Bio: Consultant, Consulting fee; Nabriva Therapeutics: Consultant and Investigator, Consulting fee and Research grant; Paratek Pharmaceuticals: Consultant, Consulting fee; Pfizer: Consultant, Consulting fee. T. Van Der Poll, Paratek Pharmaceuticals: Consultant, Consulting fee. P. McGovern, Paratek Pharmaceuticals: Employee, Salary. E. Tzanis, Paratek Pharmaceuticals: Employee, Salary.